2021
DOI: 10.33151/ajp.18.963
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Knowledge of Self-Regulation of Paramedics in Australia

Abstract: Introduction Since 2018, paramedics in Australia have been self-regulated under the National Registration and Accreditation Scheme (NRAS) for health professionals. While paramedics and other health practitioners are self-regulated in many jurisdictions internationally, there has been little study of the impact on practitioners of the introduction of new regulatory frameworks. Method Paramedics undertook a survey in the month leading up the commencement of self-regulation collecting both qualitative and quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Age and gender profiles largely matched the national PBA registrant data with a slight overrepresentation of males in the 35-54 age range (Paramedicine Board of Australia, 2021). Demographics from the pre-registration survey have been previously reported by the authors and were also representative of the workforce as reported at the time (Reed et al, 2021). The demographic profile of the sample is shown in Table 1.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Age and gender profiles largely matched the national PBA registrant data with a slight overrepresentation of males in the 35-54 age range (Paramedicine Board of Australia, 2021). Demographics from the pre-registration survey have been previously reported by the authors and were also representative of the workforce as reported at the time (Reed et al, 2021). The demographic profile of the sample is shown in Table 1.…”
Section: Resultsmentioning
confidence: 94%
“…In the pre-registration data, length of practice was a statistically significant factor; however, with a general rise in the sample reporting strong support for regulation, this distinction is now less pronounced (Reed et al ., 2021). The 2021 data revealed similar but slightly varied results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple data collection tools were utilised in this survey including multiple choice questions (MCQs), matrix MCQs and free text questions. The survey was deployed utilising the qualtrics platform identically to the pre-registration survey (Reed et al, 2021(Reed et al, , 2022. Ethics approval was obtained from the University of Wollongong Human Research Ethics Committee (Approval 2018/462).…”
Section: Survey Designmentioning
confidence: 99%